Aporia, dissemination, and simulacra as deconstructive tools in analyses of political agendas in selected works of Greg Bear and Joe Haldeman - Jubouri, Thamer A. (2021)
This study applied the concepts of aporia, dissemination, and simulacra from a deconstructive perspective to analyse the effect of political agendas in Greg Bear’s Moving Mars (1993), Vitals (2002), and War Dogs (2014) and Joe Haldeman’s Tool of the Trade (1987), The Forever War (1974), and Forever Peace (1997). The study’s gap resulted in scrutinising hidden political agendas that harness scientifically advanced weapons to destroy human lives. Therefore, the selected novels were interpreted within the wide scope of political contexts. In this regard, Bear’s Moving Mars (1993) was discussed as an allegorical work on the highly improved technology. Bear’s Vitals (2002) was approached as an exemplification of nuclear annihilation that threatens the safe existence of human race; and Bear’s War Dogs (2014) was identified through its sociological implications. As for Haldeman, his Tool of the Trade (1987) was discussed as a literary embodiment of destructive communism. Haldeman’s The Forever War (1974), furthermore, was studied via the issue of science fiction, especially the issue of arm race; and Forever Peace (1997) was interpreted in relation to the endangered destiny of humanity on the verge of catastrophic events. This danger is stimulated by the negative use of technology. The study’s significance, therefore, related to its exposing the implications of political hidden agendas after the World War II. In other words, it specifically approached postmodern political agendas by applying deconstruction, which is rarely revealed in the previous scholarship of the selected works. The study’s method, consequently, was qualitative i.e., it followed a textual analysis of the characters, settings, and narrative point of view as basic literary components to pinpoint the portrayal of hidden political agendas in the course of the selected novels by utilizing Jacques Derrida’s concepts of emporia and dissemination and Jean Baudrillard’s concept of simulacra. The study achieved three interrelated objectives. First, it examined Bear’s and Haldeman’s implied fictional discourse that depicts the negative political regimes in the post-World War II by using Derrida’s concept of dissemination. Second, it explored the selected works’ settings as imitation of real destructive military machines by applying Baudrillard’s concept of simulacra. Third, it identified Bear’s and Haldeman’s employment of the selected works’ plots as quasi-real recounts of the post-World War II’s events by using Derrida’s concept of aporia. The study’s finding revealed that fictional events resemble the reality of contemporary political agendas which are allegorically portrayed in the novels. The results and implications of the study are mainly the discursive treatment of the aftermath of the World War II and how it affected the mentality of postmodern politics. Accordingly, the study’s primary finding is that the selected novels are fictional replicas of the authentic reality of war supported by hidden political agendas which attempted to annihilate human civilisations; and the novels are utterly critiques of postmodern political atrocity. Thus, recommendations for further studies might be appropriate through applying feminism, cyber fiction, structuralism and formalism, and psychoanalysis to analyse the selected novels.